Effect of Rimsulfuron, Imazapic and Imazamox Herbicides on Broomrape (Orobanche aegyptiaca) in Tomato (Lycopersicum esculentum) - E. Kazerooni Monfared (Ikufīziyuluzhī-i Giyāhān-i Zirā̒ī, 2016)
Experiments, in Petri dish and greenhouse, were carried out to investigate the efficiency of three herbicides (rimsulfuron, imazapic and imazamox) in controling broomrape. In Petri dish study, herbicides were applied at 0.05, 0.25, 1.25, 6.25 and 31.25 micro-mole doses to broomrape seeds at germination stage without a host plant and adding GR24 as stimulator. In the greenhouse experiments, the efficiency of these herbicides to control broomrape in two varieties of tomato (Viva and Hyb.Petopride II) was investigated. Treatments were four doses of rimsulfuron (25, 50, 75 and 100 g ai/ha), imazapic (5, 10, 15 and 20 g ai/ha) and imazamox (0.4, 0.8, 1.2 and 1.6 g ai/ha) at one, two and three applications. Results of Petri-dish experiments showed that rimsulfuron and imazapic significantly reduced radicle elongation of seedlings as compared to the control, while, imazamox did not have any effect on broomrape seed. Each dose was applied for one, two and three times with in 15, 29 and 43 days after within transplanting tomato seedlings. Results of pot experiments indicated that the responses of two tomato varieties herbicides were different. Viva was responsive to herbicidal effect and produced higher biomass than Hyb.Petopride II. Rimsulfuron was a suitable herbicide in tomato to control broomrape. Rimsulfuron at doses of 25, 50 and 75 g ai/ha (three times of application) were the best doses, specially in viva were the best treatments for broomrape control and producing tomato biomass. Imazapic also, at 5 g ai/ha (two times of application) and 10 g ai/ha (single application) was an effective treatments in variety of viva. Imazamox treatments did not appear to be suitable herbicides in this study.